Preventing margin squeeze: An unsolvable puzzle for competition policy? The case of the German gasoline market - Thomas Wein (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
There is a discrepancy between Europe and the United States on whether margin squeeze is a relevant question for competition law and policy. Beyond this question, it is unclear whether law and the Cartel Office can detect margin squeeze, assuming it is necessary to look into the matter. In Germany, politicians have decided the given rule against margin squeeze should not be abolished, especially because of problems in the gasoline market. This paper discusses a comprehensive microeconomic new explanation on margin squeeze, and discusses some of the problems used to detect margin squeeze in the gasoline market. After comparing theoretical shortcuts, practical challenges and efforts towards enforcement with expected benefits, this paper concludes competition law should ignore the margin squeeze problem.
Keywords: K21; L13; L44; 330; margin squeeze; gasoline market; market dominance